Sacrificing cells of the cyst: non-apoptotic cell death in germline cysts via acidification - Bandyadka, Shruthi; Tohline, Logan; Wandji, Georgette-Vanelle; Toledano, Hila; McCall, Kimberly (Frontiers in Cell Death, 2025)
Cell death shapes multicellular organism development and sustains tissue and organ homeostasis. Great progress has been made in understanding the breadth of physiological and biochemical diversity in cell death and clearance pathways, which play vital roles in organismal development and health. While apoptosis and necrosis have been studied extensively across many model systems and contexts, the discovery of non-apoptotic paradigms of cell death and their roles in disease has greatly expanded the field. Collectively called Regulated Cell Death, these death pathways operate in a tissue and context-dependent manner. Germ cells in many organisms develop in cysts of interconnected cells, and may die in response to environmental or developmental cues. Recent findings suggest that germ cell cysts may use a common mechanism of non-apoptotic cell death involving phagocytic and lysosomal activity of surrounding somatic cells. Cyst cell death has been analyzed most thoroughly in the Drosophila adult ovary and testis, with remarkable similarity to cyst cell death in mouse adult testis and fetal ovary. In this review, we highlight recent progress in deciphering germline cyst cell death.